Unlocking the Path to Healthier Families: The Untapped Potential of Men’s Preconception Health - Muna Abed Alah (14779534) (2023)
This debate paper explores the necessity of introducing a comprehensive primary care model for men’s preconception health. It highlights the importance of a holistic approach that includes risk assessment, health promotion, and clinical and psychological interventions. Despite the current limited focus on male preconception health in primary care, there is evidence suggesting a growing awareness among men about the importance of optimizing their health before conception. The paper stresses the importance of such a model in addressing various aspects of men’s well-being, family dynamics, and overall reproductive health outcomes. It also acknowledges potential limitations and considerations related to implementing this crucial healthcare approach. Other Information Published in: Journal of Prevention License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10935-023-00762-y